2022
DOI: 10.3390/cancers14051340
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Large Granular Lymphocyte Clonal Expansions: “The Root of Many Evils”—And of Some Goodness

Abstract: Large granular lymphocyte leukemia (LGLL) is a chronic disease of either mature phenotype cytotoxic CD3+ T lymphocytes or CD3- NK cells. LGLL diagnosis is hampered by the fact that reactive persistent clonal LGL expansions may fulfill the current criteria for LGLL diagnoses. In addition to the presence of characteristic clinical and hematological signs such as anemia or neutropenia, LGLL/LGL clonal expansions have been associated with an array of conditions/disorders. We review here the presence of these persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 186 publications
1
5
0
Order By: Relevance
“…Furthermore, we found that similar phenotypical changes (most notably CD57 with co-expression of KLRG1 and a downregulation of CD5) extended to the CD4 + T cells and γδ T cells. Similarly, cases of CD4 + and γδ T cell T-LGL leukemia have been described previously, although their reported prevalence was lower than for CD8 + T-LGL leukemia ( 16 , 19 , 30 ). To our knowledge, our study represents the first instance of simultaneously investigating these phenotypical changes across the CD8 + , CD4 + and γδ T cell landscape in IBM.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, we found that similar phenotypical changes (most notably CD57 with co-expression of KLRG1 and a downregulation of CD5) extended to the CD4 + T cells and γδ T cells. Similarly, cases of CD4 + and γδ T cell T-LGL leukemia have been described previously, although their reported prevalence was lower than for CD8 + T-LGL leukemia ( 16 , 19 , 30 ). To our knowledge, our study represents the first instance of simultaneously investigating these phenotypical changes across the CD8 + , CD4 + and γδ T cell landscape in IBM.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the association between autoimmunity and T-LGLL is well-documented with approximately 15-40% of cases having concomitant rheumatic disorders including rheumatoid arthritis (RA) with Felty’s syndrome, systemic lupus erythematosus (SLE), Sjogren’s syndrome, and systemic sclerosis ( 14 , 16 , 18 ). Despite these associations, the pathological mechanisms connecting these disorders remain undetermined, although the general consensus is that chronic autoantigen stimulation drives T-LGL differentiation, transformation and persistence into a leukemic state ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clonal proliferation of T-LGLs has been detected in various clinical conditions, including autoimmune disorders, myeloid or lymphoid clonal hematologic malignancies, pure red cell aplasia, aplastic anemia, and paroxysmal nocturnal hemoglobinuria ( 29 33 ). In addition, small clonal proliferations of T-LGLs have been observed after allogeneic stem cell transplantation ( 34 , 35 ) and solid organ transplantation ( 36 38 ) as well as in patients with HIV ( 39 ) or cytomegalovirus infection ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…T‐cell clonality testing by TCR gene rearrangement is an important tool in the diagnosis of T‐cell lymphoproliferative disorders; however, interpretation of test results can prove challenging in practice given the high prevalence of clonal T‐cell proliferations in patients without underlying disease 5,7,8,11 . The presence of monoclonal T‐cell populations in non‐malignant conditions is well‐described, 12 most commonly associated with rheumatoid arthritis but also found in other conditions autoimmune conditions, including autoimmune hemolytic anemia where the clinical significance of clonal T‐cell populations remains to be elucidated 13 …”
Section: Discussionmentioning
confidence: 99%
“…The latter group underlying disease. 5,7,8,11 The presence of monoclonal T-cell populations in non-malignant conditions is well-described, 12 most commonly associated with rheumatoid arthritis but also found in other conditions autoimmune conditions, including autoimmune hemolytic anemia where the clinical significance of clonal T-cell populations remains to be elucidated. 13 Our study helps to characterize the real-world of 0.97 versus 2.78 Â 10 9 /L in patients who were treated versus untreated (Table 4).…”
Section: Methodsmentioning
confidence: 99%